Analisis Efisiensi Asuransi Umum Syariah di Indonesia Tahun 2013-2015: Aplikasi Metode Data Envelopment Analysis (DEA) - Yulia Wahyu Ningsih; Noven Suprayogi (Jurnal Ekonomi Syariah Teori dan Terapan, 2017)
This study aims to analyze the efficiency of sharia general insurance companies in Indonesia. The input variables used are total assets, expenses, and payment of claims, while the output variable is the income and tabarru’ funds. The method were used to measure the level of efficiency is the Data Envelopment Analysis (DEA) with the assumption of Variable Return to Scale (VRS) with input and output orientation. The samples are 12 sharia general insurance companies during 2013-2015. The results of the study indicate that the average result of DEA analysis for the entire DMU (Decision Making Unit) has not been efficient. The average value of economic efficiency (CRS) by 0.978, technically efficiency (VRS) for 0.925, and scale efficiency for 0.945. Source of inefficiency sharia insurance company is the scale of operations and management of input to output is not optimal.